(untitled) (Fiep Bulletin - online, 2017)
The aim of this research was to identify the prevalence of major geriatric syndromes in elderly patients who attended the department of preventive medicine of private health plan from Cascavel – PR, as well as to describe their profile and correlate with the type of geriatric syndrome. A descriptive research was chosen, in which data was collected from the elderly medical records. Data collection instrument was based on 18 questions. The elderly records who attended the medicine department from May to August 2014 were studied. There were 26 surveyed records from elderly of both genders, aged between 60 and 88 years. The prevalence was 21 females (80.77%) and 5 males (19.23%). Related to the Major Geriatric Syndromes, Cerebral failure was found, in which both, depression and memory complaints were highlighted in women; there was iatrogeny in 12 (46,15%) of the elderly studied; immobility in 3 (11,54%) women; Postural instability in 11 (42,3%) elderly and Urinary Incontinence in 14 (53,85%) of elderly of both genders. It is highlighted the seriousness of the actions and programs that health managers and the interdisciplinary team must adopt in their working process, aiming to adjust the necessary care; once it is important for them to know the routine, life habits and the diseases in which the elderly is being evaluated, as well as signs and symptoms of Geriatric Syndromes, to provide the necessary care for this part of the population.